2020
DOI: 10.1590/1414-431x20198883
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA OIP5-AS1 targets ROCK1 to promote cell proliferation and inhibit cell apoptosis through a mechanism involving miR-143-3p in cervical cancer

Abstract: Opa-interacting protein 5 antisense transcript 1 (OIP5-AS1) is one kind of cytoplasmic long non-coding RNA (lncRNA), which has been demonstrated to play a critical function in multiple cancers. However, the detailed mechanism of OIP5-AS1 in the regulation of cervical cancer progression is still obscure. Here, we demonstrated that lncRNA OIP5-AS1 was upregulated in cervical cancer and was correlated with poor prognosis by bioinformatics studies. OIP5-AS1 depletion inhibited cell proliferation and promoted cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…11 In another study, OIP5-AS1 expression is markedly upregulated in CC cells, which is significantly associated with lymph node metastasis and tumor stage. 9 Similarly, we found that MIR4435-2HG expression was dramatically increased in CC tissues and cells. Besides MIR4435-2HG expression exhibited significant correlations with FIGO stage and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…11 In another study, OIP5-AS1 expression is markedly upregulated in CC cells, which is significantly associated with lymph node metastasis and tumor stage. 9 Similarly, we found that MIR4435-2HG expression was dramatically increased in CC tissues and cells. Besides MIR4435-2HG expression exhibited significant correlations with FIGO stage and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 55%
“…10,11,26 Song et al have disclosed that down-regulation of OIP5-AS1 inhibits viability and promotes apoptosis in CC cells. 9 Zhu et al have disclosed that silencing of CDKN2B-AS1 suppresses metastasis and promotes apoptosis in CC cells. 27 Liu et al have demonstrated that inhibition of lncRNA GHET1 decreases the viability and migration ability of Figure 6 MIR4435-2HG knockdown inhibits the proliferation, migration and invasion of CC cells in vitro by regulating the miR-128-3p/MSI2 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that OIP5-AS1 and ITGA6 were upregulated while miR-92a was downregulated in OC tissues when compared with adjacent tissues. Consistently, Song et al have unveiled that OIP5-AS1 was highly expressed in cervical cancer tissues [9]. A previous study has suggested that miR-92a was downregulated in breast cancer cells [16], and it has been identi ed that the expression of ITGA6 was increased in cisplatin-resistant SKOV3 and cisplatin-resistant A2780 cells, and also in drug-resistant tissues in comparison to the controls [18].…”
Section: Discussionmentioning
confidence: 73%
“…OPA-interacting protein 5 antisense transcript 1 (OIP5-AS1) situated at chromosome 15q15.1 and is evolutionarily conserved in vertebrates [8]. OIP5-AS1 has been revealed to participate in the progression of cervical cancer [9] and breast cancer [10]. Nevertheless, the role of OIP5-AS1 in OC remains rarely studied.…”
Section: Introductionmentioning
confidence: 99%